Lo fantástico como vía de supervivencia para Ana Blandiana; vivir, recordar y soñar - Mandart, Mylène (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
Ana Blandiana, an internationally recognized writer, has been an opponent ofthe dictatorial regime of Nicolae Ceaușescu. She is a censored poet; she has had to struggleto find a way to convey her words. She became a symbol of the resistance, and despite theprohibition she continued to write; several of her tales and poems are both a reflection anda critique of how she lived under communist totalitarianism. Blandiana finds a way tolive through writing. She ties her works to the fantasy genre, which are divided betweena dream world and a historical reality. The dream is the place chosen by the writer to beable to express herself freely through the voice of her characters. In addition to the spatialduality, Blandiana chooses to situate her narratives in a temporal duality. The protagonistsare immersed in the writer’s own past, and in an eternal present through which she projectsher hopes for a better future.